WATER QUALITY AND VIBRIO DYNAMICS IN VANNAMEI SHRIMP HATCHERY AT PT DELTA WINDU PURNAMA, SITUBONDO - Dwi Saputro, Nella Azzahra; Suprakto, Bambang; Aonullah, Asep Akmal (Politeknik Kelautan dan Perikanan Dumai, 2025)
Vannamei shrimp (Litopenaeus vannamei) is a high-value aquaculture commodity. However, during the post-larval rearing phase, fluctuations in water quality and high abundance of Vibrio can cause stress and larval mortality. Therefore, evaluation of rearing practices and water quality is important to support successful juvenile shrimp production. This study aims to evaluate water quality, health, and growth of vannamei shrimp juveniles during the post-larval rearing period. Rearing was conducted from PL4–5 to PL10–11 using three tanks measuring 6 x 4 x 2 meters (water volume 40 tons), each labeled A6, B4, and B11. The fry quality results showed that all tanks achieved grade A, with optimal stadia development and gut muscle ratio. Observations on juvenile shrimp health revealed no necrosis, low Vibrio infection, and high stress resistance. Observations on post-larval growth showed an average length of 7.76–9.27 mm and an average survival rate of 88%, exceeding the minimum standard of SNI 7311:2009. Therefore, effective water quality management and control of Vibrio abundance during the rearing period of shrimp post-larvae can significantly improve the survival rate and quality of vannamei shrimp post-larvae.